Research on factors affecting green entrepreneurship intention of university students in Ho Chi Minh City - Lê, Ngọc Hải; Tran, Vinh Hoang; Tran, Thi Tuyet Mai; Tran, Hai Minh Thu; Doan, Ngoc Minh Huong (Journal of Finance - Marketing Research, 2025)
Green entrepreneurship is a topic that is currently receiving research attention from many scholars globally, as it creates new business opportunities and sustainable profits for enterprises. The objective of this article is to investigate the factors affecting green entrepreneurship intention. The authors utilized the EEM and ESM model combined with green perception to propose a research model, include: Desire, Perception of Feasibility, Seeking Opportunities, Educational Support, Environmental Support, Perception of Competitive Advantage, Environmental Values. Data were collected using the stratified sampling method from five universities in HCM City with a total of 386 students participating in the survey. The results of data analysis indicate that all proposed factors in the research model influence green entrepreneurship intention. A prominent finding of the study is the students' perception of environmental protection in entrepreneurship, demonstrated through the strong impact level of the Environmental Values factor, followed by the recognition of the Government's support policies. The research findings provide academic value to green entrepreneurship studies by emphasizing environmental protection awareness. Furthermore, the results offer a foundation for proposing managerial implications for universities to develop activities that enhance students' environmental protection perception; and for the Government to formulate support policies to establish green entrepreneurship ecosystem, thereby promoting the green entrepreneurship movement among students.